Aspek Hukum Perjanjian Kerja Dengan Kontrak Baku Antara Perusahaan Dengan Pekerja Dalam Perusahaan Satu grup : Analisis Putusan Pengadilan Negeri Medan No.132/Pdt.Sus-PHI/2016/PN.Mdn - Franz Mika Widardo Harahap; Budiman Ginting; Agusmidah Agusmidah; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. In group company, there is often a transfer of work agreements to employees from one company to another in a group of companies. Where the transfer of work agreements is made in a work agreement with a standard contract. The legal vacuum that regulates group companies opens a legal loophole that can harm other parties in general and specialy the workers who transfered to another company  within the group's companies. This certainly can eliminate the rights of employee in particular the reduction in working period because they transfered to a  different company.. This study was used to analyze the Decision of the Medan District Court No.132 / Pdt.Sus-PHI / 2016 / PN.Mdn, dated November 16, 2016 with literature support, and elaborating legislation.Legal protection has been given by the panel of judges who handle cases to employee who had the termination of employment. By declaring null and void the work agreement of a certain time of the employee and automatically making the status of permanent for employees. The panel of judges also canceled the employee's resignation letter because it was proven not because of the will of the employee but because of coercion from the company and it was proven that the employee had worked for 3 (three) years and 3 (three) months worked continuously in the same company, it was termination of employment relationship and has the right to receive severance pay and length of service awards.   Keywords: work agreements, standard contracts and group companies